What Oral Presentations Biring Into Efl Class - Zeyrek, Hasan Hüseyin (İstanbul Kültür Üniversitesi Yayınları, 2004)
Dil, bir iletişim aracıdır ve dilin en önemli ögesi de konuşmadır. Bu nedenle her İngilizce hocasının temel amacı öğrencileri İngilizce konuşmaya teşvik etmek ve dilde daha akıcı hale gelmelerini sağlamaktır. Dil öğrenen herkes öncelikle konuşma becerisi kazanmayı ve daha sonra diğer üç dil becerisi olan ‘’Dinlediğini Anlama’’, ‘’Okuduğunu Anlama’’ ve ‘’Yazma’’ becerilerini edinmek ister. Bu çalışmada ‘’Öğrenci Konuşma Süresi’’ni artırma konusunda sözlü sunumların önemi vurgulanmakta; öte yandan, bu tür sunumlar yaptırmanın zorlukları ve riskleri ele alınmaktadır.

It is the primary aim of every English teacher to encourage his students to practice their oral English and become more fluend because language is a means of communication, and its primary element is Speaking. Every languagelearner expects to learn to be able to speak the language first, then acquir the other three skills, which are Listening, Reading and Writing. In this study, the importence of oral presentations in terms of increasing Student Talking Time (STT) is emphasized. On the other hand, the frawbacks and risks of conducting Oral Presentation sessions are also pointed out.
Keywords: Oral presentations; presenting student; student talking time; communicative competence; speech fear